The Spanish reality of the professional secret of journalists: Review from the Constitution of 1978 to the present day - Barberá González, Rafael (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The professional secrecy of journalists is an element that is debated on a recurring basis. Since its appearance in the Spanish Constitution of 1978 until today, professionals, experts and leaders have expressed their opinions about its relevance, its present and the future. There have been many digressions that have been poured into different forums and with different approaches about a reality that, on occasions, goes beyond a purely professional debate.